Minimally Invasive Modified Ellison Procedure for Anterolateral Ligament Reconstruction With Biocomposite Knotless Anchor - Riccardo D’Ambrosi, M.D.; Pietro Marchetti, M.D.; Edna Skopljak, M.D.; Federico Valli, M.D.; Alessandro Nuara, M.D.; Nicola Ursino, M.D. (Arthroscopy Techniques)
In recent years, anterolateral ligament repair and lateral extra-articular tenodesis have gained prominence as adjuncts to anterior cruciate ligament reconstruction (ACLR). This renewed focus is driven by increasing reports of failure rates exceeding 20% in high-risk groups undergoing standalone ACLR. Despite advancements in surgical techniques, equipment, and postoperative rehabilitation for ACLR, unresolved rotational instability and the persistence of the pivot-shift phenomenon remain significant challenges after ACLR. However, concerns linger regarding potential complications associated with these procedures, including overconstraint of the lateral compartment, stiffness, infections, tunnel convergence, and other intra- and postoperative issues linked to extended surgical times and additional interventions. The aim of this surgical Technical Note is to present a minimally invasive, modified Ellison procedure, employing a biocomposite knotless suture anchor for tibial fixationoffering a potentially effective and less-invasive approach to address these challenges.